2022
DOI: 10.3389/fpsyg.2022.977771
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin and social gaze during a dominance categorization task in tufted capuchin monkeys

Abstract: Visual attention to facial features is an important way that group-living primate species gain knowledge about others. However, where this attention is focused on the face is influenced by contextual and social features, and emerging evidence in Pan species suggests that oxytocin, a hormone involved in forming and maintaining affiliative bonds among members of the same group, influences social attention as measured by eye gaze. Specifically, bonobos tend to focus on conspecifics’ eyes when viewing two-dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 47 publications
0
6
1
Order By: Relevance
“…Our results do not align with previous studies that have found that OT increases attentional avoidance of intact conspecific faces (Parr et al, 2013). However, these results do suggest that the two methods of manipulation influence attention differently during a dot-probe task, in support of previous literature that has also found differences between these methods (Sosnowski, Kano, & Brosnan, 2022). These results also add support to the idea that OT does not indiscriminately increase salience of all social stimuli, but instead mediates attentional avoidance specific to certain stimuli (Parr et al, 2013).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results do not align with previous studies that have found that OT increases attentional avoidance of intact conspecific faces (Parr et al, 2013). However, these results do suggest that the two methods of manipulation influence attention differently during a dot-probe task, in support of previous literature that has also found differences between these methods (Sosnowski, Kano, & Brosnan, 2022). These results also add support to the idea that OT does not indiscriminately increase salience of all social stimuli, but instead mediates attentional avoidance specific to certain stimuli (Parr et al, 2013).…”
Section: Discussioncontrasting
confidence: 99%
“…We hypothesized that experimentally manipulated OT would attenuate capuchins’ attentional bias through attentional avoidance of threatening facial expressions in the intranasal and fur-rubbing OT conditions, but predicted no effect of manipulated OT on nonsocial threatening images, based on the results of a previous study that manipulated OT in rhesus macaques (Parr et al, 2013). We predicted that the two experimental OT conditions (intranasal OT nebulization and onion-induced fur-rubbing) would yield the same effects on attention in the participants based on the results of our validation of these two methods (Benítez et al, 2018), although recent evidence that suggests different effects of the two manipulations on attentional allocation (Sosnowski, Kano, & Brosnan, 2022) indicated that this might not be the case.…”
Section: Hormonal Mechanisms Of Attentional Biases Toward Threatmentioning
confidence: 96%
“…Moreover, we do not know if the behavioral outcomes of these two inducers are the same; it may be the case that the interaction between oxytocin and subsequent behavior differs based on social context as well. Importantly, however, our results suggest a robust mechanism for exploring the impact of oxytocin on behavior using endogenously released, rather than exogenously administered oxytocin, which is increasingly important given the questions about how exogenous oxytocin is taken up (Leng & Ludwig, 2016) and how different doses may influence behavior differently (Bales et al, 2007;Peters et al, 2014;Sosnowski et al, 2022;Spengler et al, 2017). Although fur-rubbing is a relatively uncommon behavior, if the important feature is touch, it may be that we can use touch as a method for targeted induction of endogenous oxytocin release in other species as well, potentially opening new avenues for research and even therapeutic interventions.…”
Section: Inmentioning
confidence: 86%
“…As an example of one such species, capuchin monkeys ( Sapajus apella ) show a reliable increase in oxytocin following grooming and following fur-rubbing, a behavior often done in concert with conspecifics, indicating that these behaviors are serving as a bond maintenance behavior even among non-kin dyads ( 26 , 27 ). Further, as some captive capuchins are trained to complete cognitive tasks, they represent a unique opportunity to manipulate endogenous oxytocin and study subsequent changes in social attention and behavior ( 28 ). Although potentially possible in more traditional model species (for instance, many rhesus macaques are trained to complete cognitive tasks), studying species, like capuchins, with gregarious natures provides the opportunity to study how relationship quality among adults might be related to how oxytocin impacts their social decision-making in a group context (a relationship which is inconsistent and may be related to specific behavioral contexts even within a gregarious species, such as chimpanzees, Pan troglodytes : 29 , 30 ).…”
Section: The Exploration Of Oxytocin Through Different Social Systemsmentioning
confidence: 99%
“…However, these inconsistent results can be explained by a single underlying mechanism, which is oxytocin increasing the species’ natural propensities. Indeed bonobos spend more time than the other species looking at eye regions under baseline conditions ( 28 , 91 , 92 ). It is also possible that different dosages of oxytocin lead to different behaviors; there is some evidence that oxytocin’s effects may follow an inverted-U based on dosing ( 28 , 39 , 61 ).…”
Section: Oxytocin’s Variable Effects On Social Behaviormentioning
confidence: 99%